2021
DOI: 10.3390/antiox10111755
|View full text |Cite
|
Sign up to set email alerts
|

Development of Optimized Ultrasound-Assisted Extraction Methods for the Recovery of Total Phenolic Compounds and Anthocyanins from Onion Bulbs

Abstract: Allium cepa L. is one of the most abundant vegetable crops worldwide. In addition to its versatile culinary uses, onion also exhibits quite interesting medicinal uses. Bulbs have a high content of bioactive compounds that are beneficial for human health. This study intends to develop and optimize two appropriate ultrasound-assisted methods for the extraction of the phenolic compounds and anthocyanins present in red onion. A response surface methodology was employed and, specifically, a Box–Behnken design, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
3
25
2
Order By: Relevance
“…These conditions allowed us to obtain extracts of Welsh onion leaves with total polyphenols content of 51.78 mg GAE/100 g. Tomšik et al [ 43 ] obtained ethanolic Allium ursinum extracts with similar polyphenols content using the following optimal conditions for UAE: 80 °C temperature, 70% ethanol, 79.8 min, and 20.06 W/L ultrasonic power. González-de-Peredo et al [ 44 ] identified the following optimal UAE conditions to maximize the extraction of both total phenolic compounds and total anthocyanins from red onion: 50% methanol as solvent, pH 2.0, 50 °C temperature, 30% amplitude, 0.4 s cycle, and 0.2:14 g sample/mL solvent ratio.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions allowed us to obtain extracts of Welsh onion leaves with total polyphenols content of 51.78 mg GAE/100 g. Tomšik et al [ 43 ] obtained ethanolic Allium ursinum extracts with similar polyphenols content using the following optimal conditions for UAE: 80 °C temperature, 70% ethanol, 79.8 min, and 20.06 W/L ultrasonic power. González-de-Peredo et al [ 44 ] identified the following optimal UAE conditions to maximize the extraction of both total phenolic compounds and total anthocyanins from red onion: 50% methanol as solvent, pH 2.0, 50 °C temperature, 30% amplitude, 0.4 s cycle, and 0.2:14 g sample/mL solvent ratio.…”
Section: Resultsmentioning
confidence: 99%
“…A Box-Behnken design (BBD) is a kind of experimental design commonly used to optimize successfully experimental variables [ 22 , 23 ]. In this work, it was employed to measure the effect of three independent variables: modulation amplitude (×1), step potential (×2), and interval time (×3) on the determination of Trp using DPV.…”
Section: Methodsmentioning
confidence: 99%
“…It is used as a raw food and in different cooked forms, e.g., baked, boiled, braised, grilled, fried, etc. [ 8 ]. In recent years, global onion production has increased by at least 25% [ 7 , 9 ], which is linked not only to the use of onions as a flavored vegetable or spicy ingredient, but also to the use of onions as a source of bioactive phytonutrients [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, global onion production has increased by at least 25% [ 7 , 9 ], which is linked not only to the use of onions as a flavored vegetable or spicy ingredient, but also to the use of onions as a source of bioactive phytonutrients [ 9 , 10 ]. It is known that onions are rich in antioxidant compounds, and that their consumption contributes to the prevention of certain diseases associated with oxidative stress, and numerous epidemiological studies have confirmed that regular onion consumption reduces the incidence of various forms of cancer, along with cardiovascular and neurodegenerative diseases [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%